Towards Quality Education: An Entrepreneurship Education Program for the Improvement of Self-Efficacy and Personal Initiative of Adolescents - Martín-Gutiérrez, Ángela; Montoro-Fernández, Elisabet; Domínguez-Quintero, Ana (Social Sciences, 2024)
In recent decades, youth unemployment has been the focus of attention of international and community bodies in the area of social rights. Specifically, there is a need to promote attitudes and skills to access employment, decent work, and entrepreneurship. The measures implemented have not been effective. In 2023, Spain had the highest youth unemployment rate in the European Union (29.6%). An improvement in the level and quality of education and training of young people would reduce their level of unemployment. Entrepreneurship education is, therefore, a necessary value in the society of the 21st century since it is a tool for the development and growth of the younger population. In the entrepreneurship education model proposed in this study for adolescents, we focus on the capacities of self-efficacy and personal initiative as precursors of entrepreneurial behavior. This paper analyzes the differences between the mean values of the variables before and after the implementation of the educational program and the influence or correlation between the variables. The main results are threefold: (i) the educational program implemented improves the mean values of the two variables analyzed; (ii) self-efficacy exerts a positive or direct influence on personal initiative, and (iii) the educational program improves or reinforces the positive influence of self-efficacy on personal initiative.
Keywords: entrepreneurship education; program; self-efficacy; personal initiative; adolescents; social rights; youth unemployment; quality education